Adsorption Properties of Lactobacillus plantarum on the Bongkrekic Acid - Peng LIU; Wen ZHANG; Jie OU; Bailin LI (Shipin gongye ke-ji, 2023)
In order to explore the adsorption characteristics and influencing factors of bongkrekic acid by Lactobacillus plantarum X1. High performance liquid chromatography was used to determine the adsorption rate of bongkrekic acid. Factors that affect the ability of the strain to remove bongkrekic acid included time, temperature, pH, bacterial concentration, bongkrekic acid concentration and simulated gastrointestinal environment. Thermodynamic and kinetic equations were used to fit the analysis results. Results showed that the strain adsorbed bongkrekic acid quickly and efficiently and the adsorption reached saturation at 1 h. The increase of temperature, bacterial concentration and bongkrekic acid concentration enhanced the adsorption and desorption was difficult after adsorption. The optimum adsorption conditions were the temperature of 37 ℃, bacterial concentration of 6 g·L−1 and bongkrekic acid concentration of 10 mg·L−1, the adsorption rates were 52.70%, 54.12% and 48.53%, respectively. Acidic environment was favorable for BA adsorption, but the adsorption effect in simulated gastrointestinal environment was reduced due to the action of protease. The adsorption capacity reached the maximum at pH3. The adsorption process conformed to Langmuir equation and Lagergren pseudo-second order equation, and it was monolayer adsorption. The thermodynamic data were analyzed and it was found that both physical adsorption and chemical adsorption existed in the adsorption process. The whole process was spontaneous and exothermic. Therefore, Lactobacillus plantarum X1 should be potential candidates as a biological detoxification agent for the remove of bongkrekic acid via their physical binding.